Critical Thinking: Developing the Intellectual Tools for Social Justice, 1st edition - Zornado, Joseph (Routledge, 2020)
Critical Thinking presents, defines and explains the intellectual skills and habits of mind that comprise critical thinking and its relationship to social justice. Each of the sequential chapters includes detailed examples and learning exercises that guide the reader step by step from intellectual competency, to critical thinking, to cultural cognition, and to critical awareness necessary for social justice.